RESERVATION SYSTEM PORTABLE SPEAKER ON "SPOKEMAN" ON CV. DIAN INTI SERVINDO CORE USING MICROSOFT ACCESS 2000 - Natalia Dian Novita; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2005)
By using the systems necessary to the CV. Dian Inti Servindo can facilitate the search data and preparing reports. Simplify administration in providing information services to our customers, agents and other user information. computerize this proposed system will provide the information quickly and accurately, and can facilitate the search process data at any time if needed. So for the present report inventory item code with the speakers with hearing aids can computer more efficient.